INDIAN OCEAN RIM ASSOCIATION (IORA) AS STRATEGIC FACTOR IN SHAPING INDONESIA’S IMAGINED COMMUNITY AS AN ARCHIPELAGIC COUNTRY - Teuku Rezasyah (AEGIS : Journal of International Relations, 2017)
This paper aims to analyze the importance of the Indian Ocean Rim Association (IORA) in strengthening Indonesian imagined community as archipelagic country. The idea has become more important following the rise of President Joko Widodo, who constantly pursuing maritime-oriented policies. This research will rely on official documents or literature that emphasize the status of Indonesia as an archipelagic country, as well as the international law that legitimizes Indonesia as an archipelagic country, along with  historical factors and policies of World Maritime Fulcrum in the current administration. This paper will then reveal Indonesian long hibernation as an archipelagic nation. It is through IORA Indonesia works strongly to implement its imagine community, in line with capacity to bridge the ideas leading to  the world maritime fulcrum. The results of this study indicate that there are interconnections surrounding the legitimacy of international law, the historical factors, the ongoing state policy, as well as state involvement in help establishing IORA. All ideas support the Indonesian dream of establishing its own imagined community.